A Realist Analysis of the Impact of Israeli-Palestinian Conflict on Africa’s International Relations - Onome Odokuma (PERSPEKTIF, 2025)
The Israeli-Palestinian conflict has long been a significant issue in global politics, with its effects reaching beyond the Middle East. This study examined the origins of the conflict, the roles of various international organizations in peace mediation, and the impact on Africa's international relations, particularly its economic and political dimensions. Using a historical approach, the study analyzed the conflict's genesis, effects, and Africa's involvement, employing secondary data sources to explore how the conflict influences Africa, its stance, and potential strategies for resilience. The study utilized realist theory to provide an analytical framework. It concluded that resolving the conflict is essential for Africa to fully leverage its natural resources and enhance its security and economic stability. The study recommends that African nations adopt a unified position within the African Union, advocating for peaceful solutions and adherence to international law to bolster their global diplomatic influence. African nations should also, take on a more proactive role in international mediation, reinforcing peacebuilding institutions to enhance global peace and security efforts.